2021
DOI: 10.1111/ene.14704
|View full text |Cite
|
Sign up to set email alerts
|

Head‐to‐head comparison of amplified plasmonic exosome Aβ42 platform and single‐molecule array immunoassay in a memory clinic cohort

Abstract: Background and purpose Various blood biomarkers reflecting brain amyloid‐β (Aβ) load have recently been proposed with promising results. However, to date, no comparative study amongst blood biomarkers has been reported. Our objective was to examine the diagnostic performance and cost effectiveness of three blood biomarkers on the same cohort. Methods Using the same cohort (n = 68), the performances of the single‐molecule array (Simoa) Aβ40, Aβ42, Aβ42/Aβ40 and the amplified plasmonic exosome (APEX) Aβ42 blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Owning to the invasive procedure of CSF examination and high cost of PET image, blood-based assessments with comparable accuracy in predicting cerebral pathology of AD are urgently needed, especially in population screening. However, even previous studies demonstrated that plasma Aβ could be useful as a potential surrogate for brain Aβ pathology, the performances were not sufficient and discrepancies remained ( Janelidze et al, 2016 ; Verberk et al, 2018 ; Vergallo et al, 2019 ; De Meyer et al, 2020 ; Tanaka et al, 2021 ). In our current study, we explored the predictive values of plasma Aβ for Aβ-PET positive in NC, SCD, MCI, and dementia, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Owning to the invasive procedure of CSF examination and high cost of PET image, blood-based assessments with comparable accuracy in predicting cerebral pathology of AD are urgently needed, especially in population screening. However, even previous studies demonstrated that plasma Aβ could be useful as a potential surrogate for brain Aβ pathology, the performances were not sufficient and discrepancies remained ( Janelidze et al, 2016 ; Verberk et al, 2018 ; Vergallo et al, 2019 ; De Meyer et al, 2020 ; Tanaka et al, 2021 ). In our current study, we explored the predictive values of plasma Aβ for Aβ-PET positive in NC, SCD, MCI, and dementia, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…A similar technique applied by some studies is known as immunoprecipitation-free liquid chromatography-mass spectrometry (IP-free LC-MS), which measures Aβ species with mass spectrometry, but without antibody purification prior to measurement by LC-MS [22,34]. Studies that use a bead-based immunoassay, for example, the SIMOA assay or some high-sensitivity chemiluminescence assays, use beads for specific Aβ species antibody binding and indirect quantification, sometimes after amplification [20,22,28,[35][36][37][38][39][40]. In contrast, other studies apply plate-based immunoassays (such as an ELISA assay), in which a binding antibody is adsorbed onto a plate where it binds the Aβ species, and a second antibody binds to another Aβ antigen, forming what is known as a "sandwich" between the two antibodies [22,25,28,36].…”
Section: Resultsmentioning
confidence: 99%
“…In general, the immunoassays displayed lower AUCs across most studies that used a PET reference standard. Studies using a SIMOA assay had a weighted average AUC value of 0.690 across ten cohorts [20,22,24,28,[35][36][37], chemiluminescence assays had a weighted average AUC of 0.818 across six cohorts [22,28,38,40], IP-free LC-MS assays had a weighted average AUC of 0.742 across five cohorts [22,34], and ELISA assays had a weighted average AUC of 0.734 across three cohorts [22,25,36] (Table 1, Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that plasma amyloid-β examined using the Simoa immunoassay could be useful as a potential surrogate for brain Aβ pathology, though the performances were not su cient and discrepancies remained (6,7,9,38,39). In the present study, relationships between plasma amyloid-β and 18F-orbetapir SUVR were assessed not only in all the subjects with Aβ-PET scan, but also in subjects with different Aβ-PET status.…”
Section: Discussionmentioning
confidence: 63%